2021
DOI: 10.1038/s41396-021-01060-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin drives assembly of the phyllosphere microbiome and promotes disease resistance through structural and chemical cues

Abstract: The plant hormone cytokinin (CK) is an important developmental regulator, promoting morphogenesis and delaying differentiation and senescence. From developmental processes, to growth, to stress tolerance, CKs are central in plant life. CKs are also known to mediate plant immunity and disease resistance, and several classes of microbes can also produce CKs, affecting the interaction with their plant hosts. While host species and genotype can be a driving force in shaping the plant microbiome, how plant developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 103 publications
1
43
0
Order By: Relevance
“…We previously demonstrated that high CK content, or increased CK sensitivity, both support an increase in phyllosphere community richness, Shannon index, and in the proportion of Firmicutes [ 16 ]. Generally, CKs are thought to be synthesized mainly in the roots and transported via the xylem to the shoots, where they exert developmental functions [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that high CK content, or increased CK sensitivity, both support an increase in phyllosphere community richness, Shannon index, and in the proportion of Firmicutes [ 16 ]. Generally, CKs are thought to be synthesized mainly in the roots and transported via the xylem to the shoots, where they exert developmental functions [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…pFIL >> IPT and clausa have increased percentages of bacilli in the microbial community in both the seedling (Fig. 3 A, B) and mature [ 16 ], (Fig. 3 A, C) stages, and, unlike in the background M82 (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations